CONSIDERATIONS ON THE PHENOMENON OF DOUBLE TAXATION IN THE EUROPEAN UNION - ALICE CRISTINA MARIA ZDANOVSCHI (Challenges of the Knowledge Society)
In the general context of economic globalization, international economic cooperation, the liberalization movement of goods, services, capital and persons, and the effect of the exercise of fiscal sovereignty, appears the phenomenon of double or multiple international taxation of income and assets, following the vocation of several legal systems, which contain legislative differences and can generate tax obstacles, such as, the laws of the country of origin of the revenue and the legislation of the country of destination of income. Thus, more interesting becomes the study of the phenomenon of double taxation at EU level given the distinct presence of 27 sovereignties in full process of European integration So, this paper aims to identify how the European Union handles the phenomenon of double taxation, making a shift from defining this phenomenon to identifying the legislation designed to avoid or eliminate the phenomenon of double taxation in the field of EU direct taxation.Also, this paper deems necessary to stop a moment upon the fiscal harmonization and integration in the indirect taxation field of the European Union.